A complex of oxidised chitosan and silver ions grafted to cotton fibres with bacteriostatic properties. (15th June 2021) - Bian, Nengyuan; Yang, Xiaoli; Zhang, Xinli; Zhang, Fangdong; Hou, Qingxi; Pei, Jicheng
Graphical abstract: Highlights: Cotton fibres and bacteriostatic agents were combined by ester bonds. XPS was used to detect the presence of silver ions in bacteriostatic agents. Bacteriostatic fibre had excellent washing durability. Abstract: The laccase/TEMPO system was employed to oxidise the C6 primary hydroxyl group on the chitosan (CS) to form a carboxyl group to obtain oxidised chitosan (C-COS). The silver-oxidised chitosan complex(C-COS-Ag) was prepared by reacting C-COS with silver nitrate, then C-COS-Ag and cotton fibres were subjected to a reaction to prepare bacteriostatic fibres. FT-IR and XPS analysis showed that: Ag + and C-COS were combined in these forms: Ag, [Ag(NH3 )2 ] OH, -COOAg, and Ag2 O. C-COS-Ag was combined with cotton fibres by way of ester bonds. The inhibition zone of bacteriostatic fibres was all greater than 11 mm. After 50 washing tests, the bacteriostatic effect of bacteriostatic fibres remained at above 99 %. The amount of silver ions that had migrated from the bacteriostatic fibre was 3.336 mg/kg.